Diagnosis and classification of Mirizzi syndrome - I. N. Mamontov (Клінічна хірургія, 2020)
Objective. To determine the factors, predisposing to development of Mirizzi syndrome; to improve diagnosis and classification of it, taking into account of these factors and possibilities to apply a definite kind of endoscopic or operative treatment.